The restructuring of old industrial areas in East Asia. Issue 2 (4th May 2018) - Hassink, Robert; Hu, Xiaohui; Shin, Dong-Ho; Yamamura, Sakura; Gong, Huiwen
ABSTRACT: The shift of manufacturing industry from Japan, the first industrializing nation in East Asia, to neighbouring South Korea and China saw the emergence of restructuring problems and policies in traditional industries and regional economies depending on them. Based on a literature review on this topic in East Asia, this paper draws three conclusions. First, the resource endowments of the three countries differ greatly and consequently also the magnitude of restructuring problems. Second, governments in all three countries strongly affect restructuring processes, albeit with different policies and at different spatial scales. Third, although many studies have a strongly applied, policy-oriented character, recent research, particularly in China, has started to use evolutionary theories and to engage with debates of mainstream economic geography.